Avaliação do risco de incidentes: procedimento proativo para apoio à gestão da segurança do trabalho - Resende, Rodrigo Marcacine (2021)
It is estimated that occupational accidents can cost around 4% of the Gross Domestic Product (GDP) of Brazil, however, the most valuable component cannot be estimated, given the suffering that the worker and his family endure when misfortunes occur. In this sense, organizations face challenges in the search for better results for safety management, especially in acting proactively in learning from incidents, having to suffer the consequences of serious injury and fatality. From this context, the general objective of this work is to classify the incidents with the use of risk management techniques, to develop a proactive support procedure and aid in the decision making of the management of safety at work. First, the theoretical foundation was carried out, with concepts from the literature considered essential for the development of the research and the bibliographic review to evaluate studies related to the theme of this work. Subsequently, data were collected from work incidents that occurred in the last 3 years in construction and maintenance activities of electricity distribution and related activities of a company in the electricity sector and classified according to their generating situation and potential of risk (severity and frequency). The results were then expressed in the form of graphs, tables, statistical descriptions of the chi-square test, calculation of the mean time between critical incidents, in addition to the construction of the pyramid of safety events. This work observed that the assessment of the risk of incidents (accidents, near misses and deviations) from a risk matrix and its prioritization are relevant for the strengthening of safety management and that some incidents must be flagged as critical, such as those with significant capacity to generate fatalities. It is also worth noting that the results of incident analysis should be disseminated to the workforce with the aim of raising awareness. Therefore, an assessment of the risk potential of incidents can be used as a proactive procedure to identify areas where safety resources need to be directed in order to prevent serious injury and fatality.